Efektivitas Perlindungan Udang Vaname (Litopenaeus vannamei) terhadap Infeksi White Spot Syndrome Virus (WSSV) dengan Suplementasi Natrium Alginat Sargassum sp. Dari Perairan Lampung dan Kombinasi dengan Vitamin C - Muhammad Darmawan; Agus Setiawan; Ni Luh Gede Ratna Juliasih; Hilma Putri Fidyandini (Journal of Tropical Marine Science, 2023)
White spot syndrome virus (WSSV) is a viral infectious disease that can cause high mortality in Pacific white shrimp culture. The shrimp (±19 g) were reared in 9 containers with a density each of 10 shrimp/container and fed with shrimp feed at 3% of biomass daily. Shrimp were grouped into three treatments each with triplicate, namely feeding without alginate supplementation as a control, supplementation with sodium alginate supplementation of Sargassum sp. with a dose of 1 g/kg of feed + 0.2 g/kg feed of vitamin C, and supplementation of sodium alginate Sargassum sp. at a dose of 2 g/kg of feed. After 14 days of treatment, shrimp were injected with white spot syndrome virus filtrat in phosphate buffer saline (PBS) (1:1 v/v) for challenge assay. Several parameters were observed included survival rate (SR), relative percent survival (RPS), mean time to death (MTD), shrimp behaviour and clinical symptoms, hepatopancreatic histology, confirmation of white spot syndrome virus infection by PCR, and water quality. The results showed that supplementation of sodium alginate Sargassum sp. protected shrimp against white spot syndrome virus 14.80 hours longer in survival compared to the control group. However the supplementation of sodium alginate Sargassum sp. from Lampung waters not yet to protect shrimp against white spot syndrome virus after 72 hours infection.